Citizen Science: Schoolteachers’ Motivation, Experiences, and Recommendations - Aristeidou, Maria; Lorke, Julia; Ismail, Nashwa (International journal of science and mathematics education, 2023)
Citizen science offers teachers a way to bring authentic scientific research into their classrooms by providing both teachers and their students with opportunities to contribute to authentic research. The potential of citizen science for science education has already been highlighted in various fields and by various stakeholders. More and more studies underpin this potential by providing evidence for the learning outcomes achieved through participation in citizen science projects. In formal education settings, teachers are the gatekeepers for teaching innovations and, hence, the ones who decide whether to engage students in citizen science. However, the expertise of teachers who have already participated in citizen science with their students has not been studied on a broad international level. Therefore, to investigate their experience and learn from their expertise, this study employed a concurrent triangulation design and invited teachers to participate in a survey ( N = 56) and an interview ( N = 11), independent of their country of residence, their school type, and their teaching subject. The results provide insights into teachers’ motivation, the engagement techniques and types of activities they used, the challenges they faced, and their recommendations for implementing citizen science in formal education settings. The present findings have important implications for the design of professional development programmes and support networks for teachers in citizen science.